2014
DOI: 10.1108/ajim-01-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Internet use by international graduate students in the USA seeking health information

Abstract: Purpose – Considering that the internet is a useful source for health information, especially by foreign-born students, this exploratory study aimed to investigate international graduate students' internet use in the context of seeking health information. Design/methodology/approach – Data were collected from 54 Korean graduate students in the USA using a survey questionnaire. Quantitative analysis using SPSS was conducted to describe Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
1
28
1
Order By: Relevance
“…In facilitating education advocacy, showed that students (graduates and undergraduates) seek information from different social media platforms in the academic context. For instance, Facebook and Renren (the Chinese version of Facebook) play an important role in the adjustment and educational adoption of international students in seeking academic and health information from the social media (Oh et al, 2013;Yoon and Kim, 2014). The role of social media in the education advocacy is further shown in a research by Shahraniza et al (2014) who found that adjustment problems have an effect on the academic performance of international students.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In facilitating education advocacy, showed that students (graduates and undergraduates) seek information from different social media platforms in the academic context. For instance, Facebook and Renren (the Chinese version of Facebook) play an important role in the adjustment and educational adoption of international students in seeking academic and health information from the social media (Oh et al, 2013;Yoon and Kim, 2014). The role of social media in the education advocacy is further shown in a research by Shahraniza et al (2014) who found that adjustment problems have an effect on the academic performance of international students.…”
mentioning
confidence: 99%
“…Furthermore, medical treatment for international students is another issue. For them, medical treatment is very expensive as non-citizens rarely benefit from the medical incentives given to the local population, thus leading international students to seek health-related information from the internet or social media (Yoon and Kim, 2014).…”
mentioning
confidence: 99%
“…H. Lim & Kim, 2012;McKinley & Ruppel, 2014;Mou & Cohen, 2014;Neal et al, 2011;Nustad et al, 2008;Oh & Kim, 2014;Payton et al, 2014;Percheski & Hargittai, 2011;Rowley et al, 2015;Scott et al, 2008;Selkie et al, 2011;Senkowski & Branscum, 2015;Skinner et al, 2003;Smart et al, 2012;Tsan & Day, 2007;Van Velsen et al, 2012 Credibility and reliability of information (content or message), information sources, information providers or websites. Bansal & Gefen, 2010;Batten & Dutton, 2011;Catellier & Yang, 2012;Cho et al, 2015;Dutta-Bergman, 2004;Eastin, 2001;Escoffery et al, 2005;Freeman & Spyridakis, 2004;Gray et al, 2005;Hansen et al, 2003;Henderson et al, 2009;Horgan & Sweeney, 2010;Hu & Sundar, 2010;Johnson et al, 2015;Longman et al, 2012;Oh & Kim, 2014;Pariera, 2012;Rains & Karmikel, 2009;Rowley et al, 2015;Worthington et al, 2015;Yoon & Kim, 2014 Feelings, perceptions, and attitudes towards online health information. Borzekowski et al, 2006;…”
Section: Table 1 Researchers' Notions Of Trustmentioning
confidence: 99%
“…For example, demographic, psychological, socio‐cultural, and source‐, system‐ and content‐related aspects have been found to explain individuals' information seeking and use in a number of quantitative investigations (e.g., Al‐Samarraie, Eldenfria, & Dawoud, ; Khosrowjerdi & Sundqvist, ; Niu & Hemminger, ; Rowley, Johnson, & Sbaffi, ; Zimmer & Henry, ). Several studies bring forth culture as an antecedent of information related activities (Catellier & Yang, ; Jemielniak & Wilamowski, ; Neumark, Lopez‐Quintero, Feldman, Hirsch Allen, & Shtarkshall, ; Oh & Kim, ; Yoon & Kim, ). An overarching definition depicts culture as “the set of shared attitudes, values, goals, and practices that characterizes an institution … a racial, religious, or social group” (Merriam‐Webster Dictionary, ).…”
Section: Introductionmentioning
confidence: 99%